2020
DOI: 10.1002/ppul.24601
|View full text |Cite
|
Sign up to set email alerts
|

Test for respiratory and asthma control in preschool kids in the emergency department as a predictor of wheezing exacerbations

Abstract: Objective The test for respiratory and asthma control in kids (TRACK score) is a standardized questionnaire tool validated to identify poor symptom control in children with stable preschool wheeze. This study determined if TRACK score measured within 5 days of an Emergency Department (ED) visit for acute wheezing predicts a subsequent wheezing exacerbation requiring an ED visit and/or treatment with systemic corticosteroids within 3 months. Methods This was a single‐center prospective cohort study of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, the TRACK score in previous studies was an assessment of the current situation, a cross-sectional comparison. A 3-month prospective cohort study conducted by Harel-Sterling et al showed that 60 was also the best predictor of wheezing exacerbations for pre-schoolers who visited the emergency department (ED) for wheezing ( 17 ). The best cut-off point of TRACK score in prognostic prediction should be further discussed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the TRACK score in previous studies was an assessment of the current situation, a cross-sectional comparison. A 3-month prospective cohort study conducted by Harel-Sterling et al showed that 60 was also the best predictor of wheezing exacerbations for pre-schoolers who visited the emergency department (ED) for wheezing ( 17 ). The best cut-off point of TRACK score in prognostic prediction should be further discussed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the ethics board of the Hospital for Sick Children (REB #:1000053791) and the Medical University of Vienna (EK Nr 2302/2016). Additionally, 42 children with sensitizations were selected from the Wheezy ER study on pre‐school asthma between 3 and 6 years of age (REB #:1000041089), based on inclusion criteria reported previously 16,17 . These children presented to the Emergency Department at the Hospital for Sick Children with an acute wheezing exacerbation, a history of at least two wheezing episodes during the last 12 months, and displayed sensitization to food and/or inhalant allergens 18 …”
Section: Methodsmentioning
confidence: 99%
“…a personal FeNO device, and a dedicated smartphone app, has been shown to improve asthma control and the quality of life of asthmatic patients [183,184]. The Biomedical Real-Time Health Evaluation (BREATH) platform is a similar tool that focuses on pediatric patients [185].…”
Section: Discussionmentioning
confidence: 99%
“…An advanced monitoring tool, the myAirCoach system, which includes an inhaler adapter, an indoor air-quality monitor, a physical activity tracker, a portable spirometer, a personal FeNO device, and a dedicated smartphone app, has been shown to improve asthma control and the quality of life of asthmatic patients [183,184]. The Biomedical Real-Time Health Evaluation (BREATH) platform is a similar tool that focuses on pediatric patients [185].…”
Section: Risk Scoresmentioning
confidence: 99%